The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/olq.0000000000000089
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Trichomonas vaginalis and Bacterial Vaginosis and Vaginal Shedding of HIV-1 RNA

Abstract: T. vaginalis and BV were independently and synergistically related to vaginal shedding of HIV-1 RNA. Screening and prompt treatment of these 2 conditions among HIV-positive women are important not only clinically but for HIV prevention, as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 54 publications
(35 reference statements)
1
25
0
2
Order By: Relevance
“…A decrease in lactobacillus and the growth of M. hominis can increase the viral load in genital HIV by up to 100 times, which is not seen with C. albicans , suggesting that microorganisms differ in terms of their influence on HIV . Bacterial vaginosis independently influences the presence of HIV‐RNA in vaginal discharge, and is synergistically associated with trichomoniasis, as seen in the odds ratio of 4.07 presented by Fastring et al . In 17.5% of cases, the presence of trichomoniasis is associated with bacterial vaginosis, and is also related to a higher risk of HIV transmission and seroconversion …”
Section: Literature Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in lactobacillus and the growth of M. hominis can increase the viral load in genital HIV by up to 100 times, which is not seen with C. albicans , suggesting that microorganisms differ in terms of their influence on HIV . Bacterial vaginosis independently influences the presence of HIV‐RNA in vaginal discharge, and is synergistically associated with trichomoniasis, as seen in the odds ratio of 4.07 presented by Fastring et al . In 17.5% of cases, the presence of trichomoniasis is associated with bacterial vaginosis, and is also related to a higher risk of HIV transmission and seroconversion …”
Section: Literature Summarymentioning
confidence: 99%
“…The literature review identified 108 articles that associated sexually transmitted infections with HIV‐infected women. Among these articles, 33 were chosen based on the abstract and 9 were excluded owing to the criteria given above, leaving 24 articles in the analysis . The results from these articles on the influence of HIV on the prevalence, course, and treatment of other sexually transmitted infections are synthetized in Table .…”
Section: Literature Summarymentioning
confidence: 99%
“…When studying the outcome of human-microbe interactions, a complex interplay among viruses, bacteria and archaea, microbial eukaryotes, and animal parasites influence the health status of the human host, with mucosal microbiota playing a key role influencing health and disease status [60,61]. Based on these considerations and examples, trichomonads may be more prevalent and have a wider pathological spectrum in humans than currently recognized, influencing human health through direct pathologies but also indirectly through dysbiosis of the mucosal microbiota and local inflammation, facilitating transmission of pathogens -a prime example being T. vaginalis infection and bacterial vaginosis contributing to HIV transmission [61,62]. The potential influence of gut trichomonads to human health will also have to consider their potential impact on the gut microbiota, which might explain observations of the association between D. fragilis and IBS through inducing gut dysbiosis [35].…”
Section: Reviewmentioning
confidence: 99%
“…For other antiretrovirals that target the virus directly (integrase inhibitors, protease inhibitors, nonnucleotide reverse transcriptase inhibitors), the number of cell targets may be less predictive. Inflammation may, however, facilitate viral replication (and therefore number of viral particles), as increased HIV shedding in the genital tract has been correlated to increased inflammation in the presence of coinfections …”
Section: Role Of Inflammation and Coinfections In Regulating Drug Effmentioning
confidence: 99%
“…Inflammation may, however, facilitate viral replication (and therefore number of viral particles), as increased HIV shedding in the genital tract has been correlated to increased inflammation in the presence of coinfections. 48 Systemic inflammation can alter drug metabolism by regulating the expression and activity of drugmetabolizing enzymes and transporters, leading to altered pharmacokinetics. 49,50 The majority of data available are derived from in vitro or animal studies with limited data from human tissues.…”
Section: Role Of Inflammation and Coinfections In Regulating Drug Effmentioning
confidence: 99%